Structure and productivity of a 20-year-old stand of Rhizophora apiculata Bl. mangrove forest. - Ong, Jin-Eong; Gong, Wooi Khoon; Clough, B. F. (Wiley, 1995)
Mangroves are dominant interface ecosystems between the land and the sea in the tropics, and are of importance in the economy of many of these regions in terms of mangrove-linked fisheries and forestry.